Anorectal Malformations: The Pivotal Role of the Good Clinical Practice - Filomena Valentina Paradiso; Sara Silvaroli; Riccardo Rizzo; Lorenzo Nanni (Case Reports in Pediatrics)
Anorectal malformations (ARM) without a fistula are a rare congenital condition. Although may seem more simple to repair compared with ARM with fistulas, surgery has proved to be challenging. We report the case of a newborn who presented a well-formed anus and normal genitalia; a blind-ending anal canal was detected after the insertion of a rectal probe, thus allowing the diagnosis of ARM. Anal probing straight after birth avoids the possible complications related to intestinal obstruction due to a missed diagnosis of ARM. Examination of the perineal region is an important step in the evaluation of the newborn and represents the tool for a prompt identification of ARM. Adding anal probing to accurate inspection perineum is a good clinical practice and should always be performed even in presence of a normal-looking perineum.